The effect of hydrogen additives on fuel consumption and hydrocarbon emissions in gasoline fuelled Wankel rotary engine - Levin Yuriy; Fedyanov Evgeny; Gurulev Dmitrii; Itkis Evgeny (E3S Web of Conferences, 2023)
Experimental data for Wankel rotary engine performance on hydrogen blends with hydrocarbon fuel is presented. Researches are performed on partial loads and idle. Hydrogen mass fraction additions to the fuel mixture didn’t exceed at partial loads 5% and idle mode 9%. The excess air ratio was stoichiometric. It is shown that for partial loads (20% of full load) and engine speed 2000 rotary per minute 5% hydrogen addition yields to 4.2% decrease of brake specific fuel consumption (hydrogen consumption was converted to gasoline consumption computed proportionally to their combustion heats ratio). Amount of unburned hydrocarbons for the conditions mentioned reduces in a factor of 1.8 and emission of carbon monoxide in a factor of 2.3. Hydrogen addition notably increase effective leaning limit, thus for idle mode tests Wankel rotary engine showed steady performance even for excess air ratio 1.16, while in the absence of addition instability displayed itself for excess air ratio exceeding 0.95.